1987
DOI: 10.1172/jci113071
|View full text |Cite
|
Sign up to set email alerts
|

Defective in vitro growth of the hemopoietic progenitor cells in the acquired immunodeficiency syndrome.

Abstract: In addition to immunologic derangement, hematological abnormalities have been reported in the majority of patients with ac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(52 citation statements)
references
References 39 publications
6
46
0
Order By: Relevance
“…While the precise mechanisms of such hematopoietic abnormalities remain unclear, several hypotheses have been proposed: (i) decreased levels of appropriate cytokines secondary to altered numbers of T-cell subsets or macrophages, which are commonly seen in HIV type 1 (HIV-1) infection (28); (ii) production of inhibitory factors (14,29); (iii) cytotoxic elimination of the precursor cells by the antibody-dependent cellmediated cytolytic mechanism (7); and (iv) infection of hematopoietic precursor cells with viruses, which leads to death of these cells or their metabolic alteration (7). On the other hand, it has been suggested that primitive bone marrow progenitor cells are most likely not a major reservoir for HIVs (6,13,28).…”
mentioning
confidence: 99%
“…While the precise mechanisms of such hematopoietic abnormalities remain unclear, several hypotheses have been proposed: (i) decreased levels of appropriate cytokines secondary to altered numbers of T-cell subsets or macrophages, which are commonly seen in HIV type 1 (HIV-1) infection (28); (ii) production of inhibitory factors (14,29); (iii) cytotoxic elimination of the precursor cells by the antibody-dependent cellmediated cytolytic mechanism (7); and (iv) infection of hematopoietic precursor cells with viruses, which leads to death of these cells or their metabolic alteration (7). On the other hand, it has been suggested that primitive bone marrow progenitor cells are most likely not a major reservoir for HIVs (6,13,28).…”
mentioning
confidence: 99%
“…It has been shown in vitro that a synthetic peptide homologous to a sequence of the envelope protein of HIV suppress the oxidative burst of monocytes (Harrell er fl/,, 1986), Further, the growth of precursor cells in bone marrow may be impaired in patients with HIV infection (Stella, Ganser & Hoelzer, 1987) and this may lead to functionally deficient monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…At day 1 and 10, adherent cell nuclei were counted as described by Unkeless & Eisen (1975). The detection limit of this assay was 10'' cells/well (data not shown).…”
Section: Monocyte Culturementioning
confidence: 99%
“…This may lead to anaemia and other haematologic anomalies in HIV infection [14,15]. Also, a model has been developed in which the pathophysiologic processes producing the anaemia in chronic diseases like HIV may be linked to the actions of pro-inflammatory cytokines (IL-1, TNF-α, and IFN-γ) that mediate the immune responses [16].…”
Section: Background Of Studymentioning
confidence: 99%